Analysis of Agriculture Input Consumption by Indian Farmers - Pathania, Ankit; Chaudhary, Rashmi; Kumar, Krishan (International Journal of Economic Plants, 2020)
Agriculture has always been a lifeline of the Indian economy as it provides livelihood and employment to more than 54% of the population. It also contributes around 13.9% to the gross domestic product of the country. The backbone of any agricultural revolution is the access of farmers to modern agricultural inputs. These agricultural inputs range from improved seeds, fertilizers and crop protection chemicals to machinery, irrigation and knowledge etc. Keeping this in the background, the present study was carried out to make an analysis of agricultural inputs usages by the Indian farmers. The data for the present study were mainly sourced from various government published reports like agriculture statistical at a glance, 2018 and agricultural research data book, 2018. The analysis of the information was performed using annual growth rate, percentage and compound annual growth rate from 2001-02 to 2017-18. The study resulted in that input-consumption in the agriculture sector has expanded to a large extent during the study period and showing an increasing trend in the consumption-status of most of the agricultural inputs like certified/quality seeds, fertilizers, pesticides, farm machinery and electricity. Furthermore, it can be suggested that agricultural inputs have a huge potential to scale-up and maximizing agricultural productivity in the country.